THE EFFECT OF PROBLEM SOLVING METHOD ON READING PROFICIENCY OF 9TH GRADE STUDENTS OF MTSN TANJUNG PINANG - Ihsan Abyad, Muhammad; Annas, Al-Baihaqqi (SHAWTUL ARAB, 2025)
This study investigates the impact of applying the problem-solving approach on enhancing pupils' reading abilities. This study employs a quasi-experimental design and a quantitative methodology to ascertain its findings. A nonequivalent control group design is employed as the quasi-experimental design. Twenty-five students from class IX-1 and twenty-five students from class IX-3 participated in the study, which was carried out at Mtsn Tanjung Pinang. While students in class IX-3 received therapy using the problem-solving approach under the heading "The Effect of the Problem-Solving Method on the Reading Skills of Class 9 Students of Mtsn Tanjung Pinang," students in class IX-1 received no treatment at all. This investigation was carried out at Mtsn Tanjung Pinang between June 10 and June 12, 2024. Following the post-test, the class IX. 3 Mtsn Tanjung Pinang's Arabic learning outcomes on Fiil were 83.40 out of a possible 100. The highest score was 95 out of 100. 70 out of 100 was the lowest possible score. Additionally, 6.727 was the standard deviation. Using the independent sample t-test procedure, the results of inferential analysis showed that the t-table was 2.060 and the t-count value was 4.657 with df 25 at a significance level of 5%. So that t-count > t-table, Ho is refused and Ha is approved, indicating that the usage of problem-solving procedures has an impact on class IX-3 reading skills